The Toxicology Investigators Consortium Case Registry—the 2017 Annual Report - Farrugia, Lynn A. (J Med Toxicol, 2018)
The Toxicology Investigators Consortium (ToxIC) Case Registry was established by the American College of Medical Toxicology in 2010. The Registry collects data from participating sites with the agreement that all bedside medical toxicology consultations will be entered. The objective of this eighth annual report is to summarize the Registry’s 2017 data and activity with its additional 7577 cases. Cases were identified for inclusion in this report by a query of the ToxIC database for any case entered from 1 January to 31 December 2017. Detailed data was collected from these cases and aggregated to provide information which includes demographics (e.g., age, gender, race, ethnicity), reason for medical toxicology evaluation (e.g., intentional pharmaceutical exposure, envenomation, withdrawal from a substance), agent and agent class, clinical signs and symptoms (e.g., vital sign abnormalities, organ system dysfunction), treatments and antidotes administered, fatality, and life support withdrawal data. Females were involved in 50.4% of cases. Transgender demographic information collection was initiated in 2017 to better represent the population and there were 36 cases involving transgender patients. Adults aged 19–65 were the most commonly reported age group. Non-opioid analgesics were the most commonly reported agent class, with acetaminophen again the most common agent reported. There were 93 fatalities reported in 2017. Treatment interventions were frequently reported with 30.6% receiving specific antidotal therapy. Major trends in demographics and exposure characteristics remained similar to past years’ reports. While treatment interventions were commonly required, fatalities were rare. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13181-018-0679-z) contains supplementary material, which is available to authorized users.